¿Dónde están los negros? políticas de embranquecimento sob a ótica das mulheres negras na Argentina - Barreto, Marina Leão de A. (Afro-Ásia, 2022)
Resenha de: EDWARDS, Erika. Hiding in Plain Sight: Black Women, the Law, and the Making of a White Argentine Republic. Tuscaloosa: University of Alabama Press, 2020. 168 p.